Funeralaspis n. gen.: a new odontopleurine trilobite from the early Middle Ordovician (Dapingian) of Death Valley, eastern California, USA, and the classification of Ordovician odontopleurines - Adrain, Jonathan M.; Pérez-Peris, Francesc (Zootaxa, 2023)
Funeralaspis n. gen. (type species F. deathvalleyensis n. sp.) is the oldest known formally named odontopleurine trilobite species, described on the basis of abundant secondarily silicified sclerites of all sclerite types except the rostral plate, from the Dapingian of the Antelope Valley Formation, west flank of the Funeral Range, Death Valley National Park, Inyo County, California. Many Ordovician odontopleurines have been assigned to Diacanthaspis, to the point that it has become something of a taxon of convenience. All of the potential species are listed along with their provenance, preservation, and represented sclerite types. A core group of Diacanthaspis, termed Diacanthaspis (sensu stricto or s.s.) possibly represents a Laurentian clade, consisting of the type species, D. cooperi, and D. lepidus, D. orandensis, D. scitulus, D. secretus, and possibly D. elapsa and D. parvula. This group is characterized by extreme dorsal spinosity, dorsal accessory spines on the base of the genal spine, pygidial spines with lateral fringes of tiny spines, and thoracic and pygidial ring furrows with fringes of tiny spines. Funeralaspis deathvalleyensis has none of the features characteristic of Diacanthaspis and in general scarcely resembles members of this Upper Ordovician group. Remaining species that have been assigned to Diacanthaspis, some of which are very poorly known, should be reclassified as knowledge of Ordovician odontopleurines advances, but for the present are treated as Diacanthaspis (sensu lato or s.l.). A heretofore nearly unknown species described as Ceratocephala maquoketensis from the early Katian of Howard County, Iowa, has not been commented upon in the literature since it was proposed. It is an odontopleurine which in the current state of knowledge should be assigned to the Diacanthaspis (s.l.) group.